Ground-based Characterization of (98943) Torifune 2001 CC21, the Target of the Hayabusa2# Space Mission - Marcel M. Popescu; Eri Tatsumi; Javier Licandro; Miguel R. Alarcon; Javier Rodríguez Rodríguez; Miquel Serra-Ricart; Julia de León; Joaquín Fernandez Martin; David Morate; Gabriel N. Simion; Bogdan Alexandru Dumitru; Daniel Nicolae Berteşteanu; et al. (The Planetary Science Journal)
The near-Earth asteroid (98943) Torifune, previously designated 2001 CC _21 , is the flyby target of the Hayabusa2 extended mission, nicknamed Hayabusa2 # (Small Hazardous Asteroid Reconnaissance Probe (SHARP)). The ground-based telescope observations offer a key science input for the mission's scientific investigation. During 2022–2024, this asteroid was at visible apparent magnitudes brighter than 18.5, allowing for a detailed characterization using ground-based telescope observations. We determined its rotation period P = 5.021516 ± 0.000106 hr and its absolute magnitude H = 18.78 ± 0.14. The large number of light curves allows us to estimate its axis ratio, its convex shape, and its pole orientation, λ = 301 ^∘ ± 35 ^∘ , $β =8{9}_{-6}^{+1^° }$ , and ϵ = 5 ^∘ ± 3 ^∘ , respectively, which indicate a prograde rotation. We report the semiaxis of the equivalent ellipsoid, a = 0.42 ${}_{0.06}^{+0.08}$ km, b = 0.16 ${}_{0.04}^{+0.05}$ km, and c = 0.17 ± 0.03 km. Consequently, the volume-equivalent diameter is D _eq = 0.44 ± 0.06 km. Using observations conducted simultaneously with four broadband filters, we determined ( g − r ) = 0.663 ± 0.022 mag, ( r − i ) = 0.177 ± 0.012 mag, and ( i − z _s ) = −0.061 ± 0.032 mag. Additionally, we found that Torifune exhibits no detectable large-scale heterogeneity. We classified the object using a high signal-to-noise ratio spectrum (over the visible and near-infrared region) as Sq-type in the Bus–DeMeo taxonomy. We estimate a mineralogy similar to LL/L ordinary chondrites, with an ol/(ol+px) = 0.60, a Fa content of 28.5 mol%, and a Fs content of 23.4 mol%. The spectral data indicate a surface affected by moderate space weathering effects.